PENGGUNAAN MEDIA KOMIK TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS XI - Annisa Dian Ramadhania; Sinta Rosalina; Slamet Triyadi (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
Learning media has an important role in the learning process. Learning media can help teachers to convey material in an interesting and easily understood by students. This thesis research is about the use of flood disaster comic media on the skills of writing explanatory text in class XI students of SMAN 4 Karawang. The aims of this study were to 1) describe the creation of comic media in learning to write explanatory texts for class XI students of SMAN 4 Karawang, 2) describe the use of comic media with pictures of flood disasters in writing explanatory texts for class XI students of SMAN 4 Karawang. The subjects in this study were thirty-five students of class XI IPS 3. The research object is in the form of comic media with the theme of flood disaster written by XI IPS 3 students. The research method used is descriptive qualitative. The research instrument used tests and interviews. Data analysis techniques carried out in this study consisted of data reduction, data presentation, and making conclusions. Researchers used flood disaster comic media made from A4 photo paper and paper, and the pictures were made by my friend. The results showed that the ability to write explanatory texts for class XI IPS 3 SMAN 4 Karawang using the flood disaster comic media as a whole was in accordance with the structure and linguistic rules of explanatory texts, namely 2 students were categorized as getting very good grades, 18 students were categorized as getting grades good, 1 student is categorized as getting an adequate score, and 13 students are categorized as getting a low score.